Analysis of Fishing Vessel Queueing Models for Optimizing Palabuhanratu Fishing Port Operations - Annisa Fitri; Sugeng Hari Wisudo; Tri Wiji Nurani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
This study is motivated by the importance of operational efficiency in fishing ports in addressing the dynamics of vessel arrivals and limited service facilities. The objective of this study is to analyze a fishing vessel queue model to optimize port operations at the Palabuhanratu Port based on existing facility conditions. The methods used include field observation, interviews, and quantitative analysis using a queue model with a Poisson distribution approach for vessel arrivals and an exponential distribution for service. The results of the analysis show that the queue system follows the (M/M/5):(FCFS/ / ) model with five service points operating in parallel. The vessel arrival rate is relatively low compared to the service capacity, so that the port is in an under capacity condition with a high probability of an empty system and almost no waiting time in the queue. To improve optimization, scenarios were carried out to increase the number or frequency of vessels in several vessel size categories, namely 21 vessels (21–30 GT), 63 vessels (5–10 GT), 12 vessels (11–20 GT), 123 vessels (5–10 GT), 7 vessels (51–100 GT), 5 vessels (101–200 GT), 31 vessels (5–10 GT), and 4 vessels (11–20 GT). Simulation results show that the addition is able to increase the utilization of port facilities without causing significant queues, so that operational efficiency can be improved sustainably.